NUMBER OF COLIFORM BACTERIA IN BALI CATTLE BASED ON MATURITY LEVEL AND LOCATION OF FARMS IN NUSA PENIDA - Junus, Bianca Violanda; Besung, I Nengah Kerta; Suarjana, I Gusti Ketut; Suwiti, Ni Ketut (Buletin Veteriner Udayana, 2018)
The aims of this study is to determine the effect of maturity level and location of the farms to the number of coliform bacteria in bali cattle feces in Nusa Penida. 24 samples of bali cattle’s feces were used in this research. This study used a Randomized Complete Block Design (RCBD) of 2x3 factorial consist of two location of altitude plateu (lowland and highland) and three maturity level (calves, heifers, and adult). The sample was grown on Nutrient Agar using the casting method. The obtained data were tested by analysis of variance followed by Least Significant Difference (LSD) Test. The results showed that the number of coliform bacteria in bali cattle was significantly different at maturity level and location of the farm. Number of coliform bacteria in bali cattle of the lowland was (138.66 x 10 7 CFU/g), which is higher than bali cattle on the high land (102 x 10 7 CFU/g).  Test results of LSD Test showed the number of coliform cattle calf is 43,25 x 10 7 CFU/g is lower compare to heifers 124 x 10 7 CFU/g and adults 193,75 x 10 7 CFU/g. The number of coliform bacteria in feces of heifers cattle is lower than the number of coliform bacteria in feces of adult cattle.